Crop weather relationship in arecanut - Jose, C.T.; Chandran, K. P.; Muralidharan, K.; Jayasekhar, S. (Journal of Plantation Crops, 2020)
Weather plays an important role in the crop development and yield of any agricultural crops. Even though, arecanut (Areca catechu L.) grows in a wide range of climatic conditions, its performance is greatly influenced by the weather. The effect of weather variables such as maximum temperature, minimum temperature, relative humidity and rainfall at different stages of crop development on the annual yield of arecanut is studied. The study showed that the maximum temperature positively influences the flowering and fruit set in arecanut. Also, high rainfall and relative humidity during the flowering and fruit setting period adversely affect the arecanut yield. The stepwise regression model fitted using the significant weather variables could explain 97 per cent of the yield variation in arecanut.